2011
DOI: 10.15835/nbha3926820
|View full text |Cite
|
Sign up to set email alerts
|

Microarray Analysis of the Transcriptome for Bacterial Wilt Resistance in Pepper (Capsicum annuum L.)

Abstract: Ralstonia solanacearum causes one of the most common soil-borne vascular diseases of diverse plant species, including many solanaceous crops such as tomato and pepper. The resulting disease, bacterial wilt (BW), is devastating and difficult to control using conventional approaches. The aim of this study was to investigate the differentially expressed genes in pepper root systems in response to infection by R. solanacearum. DNA microarray (Capsicum annuum 135K Microarray v3.0 Gene Expression platform) analyses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 32 publications
1
8
0
Order By: Relevance
“… Godiard et al (1991) isolated cDNA clones corresponding to mRNAs that accumulate during the early phase of the hypersensitive response in suspension cultured tobacco cells challenged with a non-pathogenic strain of R. solanacearum ( Godiard et al, 1991 ). Microarray analysis showed that R-response genes were related to xyloglucan biosynthesis and cell wall organization, while S-response genes were involved in response to stress and cell death in pepper ( Hwang et al, 2011 ). A root transcriptome provided insight into the dynamic crosstalk between peanut and R. solanacearum ( Chen et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“… Godiard et al (1991) isolated cDNA clones corresponding to mRNAs that accumulate during the early phase of the hypersensitive response in suspension cultured tobacco cells challenged with a non-pathogenic strain of R. solanacearum ( Godiard et al, 1991 ). Microarray analysis showed that R-response genes were related to xyloglucan biosynthesis and cell wall organization, while S-response genes were involved in response to stress and cell death in pepper ( Hwang et al, 2011 ). A root transcriptome provided insight into the dynamic crosstalk between peanut and R. solanacearum ( Chen et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…R. solanacearum infection in chickpea was observed to result in a mild to severe disease symptoms which include yellowing, wilting and cell death; however, it was also observed that R. solanacearum does not provoke sudden plant death in leaf-inoculated plants ( Sinha et al, 2016 ). The molecular responses of plants against R. solanacearum infection has been extensively studied ( Hwang et al, 2011 ; Ishihara et al, 2012 ; Chen et al, 2014 ; Prasath et al, 2014 ; Zuluaga et al, 2015 ); however, so far no attempt has been made to understand the transcriptomic responses of plant to combined drought and R. solanacearum infection.…”
Section: Introductionmentioning
confidence: 99%
“…To further annotate our SNPs, we also took advantage of a previous transcriptome analysis of resistance and susceptible pepper lines, which identified differentially expressed genes (DEGs) in these cultivars using Arabidopsis gene chip analysis [17]. The corresponding direct orthologs with the Arabidopsis gene ID were regarded as candidate DEGs in pepper gene model, and we identified those with non-Syn SNPs between YCM334 and Taean (Table 4).…”
Section: Resultsmentioning
confidence: 99%
“…To take advantage of a published transcriptome analysis comparing YCM334 and Taean and performed using the Arabidopsis gene chip [17], we attempted to identify pepper genes orthologous to those Arabidopsis gene IDs previously identified as DEGs in this study. For this analysis we used the PLAZA 3.0 dicot database [22].…”
Section: Methodsmentioning
confidence: 99%